A study on cyclist head injuries based on an electric-bicycle to car accident reconstruction. (14th October 2020) - Gao, Wenrui; Bai, Zhonghao; Li, Huan; Liu, Yu; Chou, Clifford C.; Jiang, Binhui
Abstract: Objective: In China, the electric-bicycle (E-bike) has become one of the most common modes of travel. However, the safety of E-bike has not received sufficient attentions, especially in the area of protection of the cyclists' head. Methods: In this study, an E-bike-to-car accident was reconstructed using MADYMO and LS-DYNA software and head injuries of the cyclist were analyzed. A multi-rigid body model in MADYMO and a head to windshield impact finite element (FE) model using LS-DYNA were separately developed to achieve objectives of the work. Results: Kinematic responses of the cyclist were predicted by the multi-rigid body model to obtain the best reconstructed results compared to those given in the accident report, and the instantaneous linear and angular relative velocities at the onset of contact between the head and windshield, which were used as input loading conditions to the FE model, were obtained. The maximum principal strain (MPS) of skull, and intracranial pressure (ICP), von-Mises stress and MPS (Maximum principal strain) of brain tissue were predicted by the FE model for the head injuries analyses. Conclusions: The results of accident reconstruction in this study case showed that: (1) The head impact region on the windshield in the E-bike-to-car impact accidents is higher than that in the pedestrian-to-car impact accidents. (2) The skull MPS, ICP, von-Mises stress and MPS of strain can accurately predict the head injury risk, location, etc. (3) The directly impact force caused the skull fracture, and the tensile inertial force torn bridge vein resulting in the subdural hematoma on the opposite side of impact in this accident. (4) The models developed in this study were validated against the reconstructed accident and can be used for further study on head injuries of E-bike's cyclist and helmet design.